Випадкові знахідки кинджалів скіфського часу у басейні Сіверського Дінця як свідчення сухопутних комунікацій - Шелехань, О.В. (My University, 2012)
O. Shelekhan. Chance Finds of the Scythian-time Daggers on the Siversky Donets Basin as Proof of the Overland Communications This article is devoted to the analysis of chance finds of the Scythian period dagger in the Seversky Donets basin. We know eight authentic specimens founded outside the archaeological complexes. All of them date from the early Scythian time. Mapping shows that the majority finds daggers drawn to the watershed of the Donets and the Dnieper. So they mark the so-called Muravsky shlyakh — land communication between the Crimea and the left-bank forest-steppe. Part of the findings lies near the Donets fords. Traced pattern correlates with the location of settlement sites of the Seversky Donets region. It is obvious that the considered traces of antiquity are not of one share, and reflect the operation Muravsky shlyakh as a coherent system is already in the 6th century BC. Interestingly the lack of random finds of the late-Scythian time. Perhaps this indicates to the establishment of the coherent relationships between nomads and settled populations.